Doing descriptive phenomenological data collection in sport psychology research - O`Halloran, L.; Littlewood, M.; Richardson, D.; Tod, D.; Nesti, M. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
Researchers in the field of sport psychology have begun to highlight the potential of phenomenological approaches in recognizing subjective experience and the essential structure of experience. Despite this, phenomenology has been used inconsistently in the sport psychology literature thus far. Therefore, the aim of this paper is to provide theoretically informed practical guidelines for researchers who wish to employ the descriptive phenomenological interview in their studies. The recommended guidelines will be supported by underpinning theory and brief personal accounts. An argument will also be presented for the potential that descriptive phenomenology holds in creating new knowledge through rich description. In doing so, it is hoped that this method will be utilized appropriately in future sport psychology research to not only strengthen and diversify the existing literature, but also the knowledge of practitioners working within the applied world of professional sport.